Corporate Governance Practices and Sustainability Performance of Commercial Banks in Nigeria - Dennis Okorie , Charles; Christopher Ebere, Chukwuma (Research Parks Publishers, 2025)
This study investigated the impact of corporate governance practices on the sustainability performance of commercial banks in Nigeria. Data was collected for the three dimensions of sustainability (environmental, social and governance) and corporate governance measured with board independence and board gender diversity. Using secondary data extracted from the audited financial reports of 12 commercial banks listed on the Nigerian Exchange (NGX) over a ten-year period, the study employed Panel Least Squares (PLS) regression analysis to examine relationships across the three dimensions of sustainability. The findings revealed that the selected corporate governance variables have minimal and insignificant effects on sustainability performance across all the dimensions sustainability. This suggests that governance mechanisms in Nigeria commercial banks may not yet be sufficiently aligned with sustainability objectives. The study recommended improving board composition to include sustainability experts and enhancing gender diversity to improve strategic decision-making. Additionally, regulatory authorities should establish clearer guidelines for integrating sustainability into governance practices, including mandatory sustainability reporting. Strengthened stakeholder engagement and the adoption of comprehensive sustainability policies are also proposed as measures to improve alignment with global sustainability goals.